Immune Response of Indian Preterm Infants to Pentavalent Vaccine Varies With Component Antigens and Gestational Age - Kulkarni-Munje, Archana; Malshe, Nandini; Palkar, Sonali; Amlekar, Aniket; Lalwani, Sanjay; Mishra, Akhilesh Chandra; Arankalle, Vidya (Frontiers in Immunology, 2021)
Childhood vaccination plays critical role in protecting infants from several dreaded diseases. Of the global 15 million preterm (PT) infants with compromised immune system born annually, India contributes to >3.5million. Generation of adequate vaccine-induced immune response needs to be ensured for their protection. Immune response of Indian PT (n=113) and full-term (FT, n=80) infants to pentavalent vaccine administered as per the national recommendation was studied. Antibody titers against component antigens of pentavalent vaccine, immune cells profiling (T and B cells, monocytes and dendritic cells) and plasma cytokines were determined pre- and post-vaccination. Additionally, cell mediated recall immune responses to pentavalent antigens were evaluated after short time antigenic exposure to infant PBMCs. Irrespective of gestational age (GA), all the infants developed adequate antibody response against tetanus, diphtheria and, protective but lower antibody levels for Haemophilus influenzae type-b and hepatitis B in preterm infants. Lower (~74%) protective antibody response to pertussis was independent of gestational age. PT-infants exhibited lower frequencies of CD4T cells/dendritic cells/monocytes, increased plasma IL-10 levels and lower proliferation of central and effector memory T cells than in term-infants. Proliferative central memory response of FT-infants without anti-pertussis antibodies suggests protection from subsequent infection. Responder/non-responder PT-infants lacked immunological memory and could be infected with Bordetella. For hepatitis B, the recall response was gestational age-dependent and antibody status-independent. Humoral/cellular immune responses of PT-infants were dependent on the type of the immunogen. Preterm infants born before 32 weeks of gestation may need an extra dose of pentavalent vaccine for long lived robust immune response.